1968
DOI: 10.1103/physrev.170.455
|View full text |Cite
|
Sign up to set email alerts
|

Knight Shifts ofC13in the Carbides of Uranium and Thorium

Abstract: The C 13 nuclear magnetic resonance has been observed in the unenriched carbides of thorium and uranium ThC, TI1C2, UC, U2C3, and UC2. In contrast to nearly all nonmagnetic metals and semimetallic compounds, the Knight shift in the semimetallic thorium carbides is negative. On the other hand, the Knight shifts in all of the uranium carbides are positive, which is consistent with the P 31 shift in UP and PrP. The C 13 Knight shift in all of the carbides except U2C3 was temperature-independent. On the basis of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0

Year Published

1969
1969
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(10 citation statements)
references
References 51 publications
3
7
0
Order By: Relevance
“…Indeed, assuming a 5f 3 ( 4 I 9/2 ) electronic configuration for the U ions, and C 3 site symmetry, Burton Lewis et al found a value of μ eff = 2.3μ B . 34 However, the information provided by a Curie-Weiss fit on a polycrystalline sample of anisotropic compound is limited, and we will not further comments on these results. With decreasing temperature, the susceptibility curve goes through a broad maximum at T * ∼ 59 K. In the temperature range from about 20 to 100 K, as shown in the lower inset of Fig.…”
Section: Resultsmentioning
confidence: 98%
“…Indeed, assuming a 5f 3 ( 4 I 9/2 ) electronic configuration for the U ions, and C 3 site symmetry, Burton Lewis et al found a value of μ eff = 2.3μ B . 34 However, the information provided by a Curie-Weiss fit on a polycrystalline sample of anisotropic compound is limited, and we will not further comments on these results. With decreasing temperature, the susceptibility curve goes through a broad maximum at T * ∼ 59 K. In the temperature range from about 20 to 100 K, as shown in the lower inset of Fig.…”
Section: Resultsmentioning
confidence: 98%
“…This treatment takes account directly of the properties of the mirrors and was discussed by deLang. 1 Other authors [2][3][4][5][6][7][8][9][10][11] …”
Section: Discussionmentioning
confidence: 99%
“…recently on 31 P in uranium phosphides, 4-8 on 14 N in uranium mononitride, 9 and on 13 C in uranium carbides. 10 Very few spin-lattice relaxation time results have been reported for nuclei in the paramagnetic state of solids that have ordered states. Only one report can be found on T\ measurements in the paramagnetic state of uranium compounds, namely, the proton spin-lattice relaxation times in the paramagnetic state of 0-UH 3 .…”
mentioning
confidence: 99%
“…11 In order to record the 14 N signals in UN, large (40-Hz) field modulations (with peak-to-peak amplitudes up to 9 Oe) were used, and signals were detected only in the dispersion mode and only by applying rf fields as high as 0.3 Oe. The same experimental conditions were used by Lewis et aL 10 in their recent NMR measurements of 13 C in uranium carbides.…”
Section: Methodsmentioning
confidence: 99%